“Biologic Restoration:” A case report of a novel method for restoration of a fractured anterior tooth (Indian Journal of Case Reports, 2018)
Anterior tooth fracture, as a result of traumatic injuries, is a common occurrence in routine dental practice. Trauma to the anterior teeth affects the physical and psychological well-being of the patient and hence, requires quick functional and esthetic repair. In spite of the advances in material science, none of the materials completely simulate the physical and mechanical properties of natural tooth structure. Henceforth, a biological restoration seems to be a successful biocompatible and cost-effective alternative approach for treating such cases. Here, we report the clinical case of esthetic and functional reconstruction of a fractured maxillary right central incisor by means of “biological restoration” using Homogenous fragment bonding associated with the cementation of biopins produced from human dentin in a 32-year-old male patient.